Kinetics and Mechanism of Oxidation of Diethyl Sulfide by Pyridinium Chlorochromate - Chellamani, A.; Glory Florance Shyla, W.; I. Emelda Velenciya Hezia, I.; Harikengaram, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of diethyl sulfide (DES) by pyridinium chlorochromate (PCC) have been studied in 50% acetic acid-50% water (v/v) mixture. The reaction is first-order each in [DES]. [PCC] and [H+]. Diethyl sulfoxide is the product of the reaction. A mechanism involving the formation of intermediate complex between protonated PCC and sulfide in a slow step has been proposed.